Super-hydrophobic radiation heat dissipation coating material and preparation method thereof
The TiC@BN compound phase powder prepared by nitriding combustion synthesis technology is combined with polymer binder, which solves the problem of difficult to develop materials in the prior art that both radiative heat dissipation, superhydrophobicity and corrosion resistance, and achieves an efficient and economical radiation heat dissipation effect of electronic devices.
Patent Information
- Application Number
- CN202411788805.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art is difficult to develop a multifunctional material that combines efficient radiation heat dissipation, superhydrophobicity and corrosion resistance, and the process is complex and difficult to produce on a large scale.
Using nitriding combustion synthesis technology, TiC@BN composite phase powder with a hierarchical structure is prepared, and combined with a polymer binder system to prepare superhydrophobic radiation heat dissipation coating material.
It achieves a combination of high infrared emissivity and superhydrophobic performance in the wide band of 2.5-25μm, and is suitable for high-efficiency and long-term radiation heat dissipation of electronic devices.
Smart Images

Figure CN119592215A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of heat dissipation coatings, and in particular to a super-hydrophobic radiation heat dissipation coating material and a preparation method thereof. Background Art
[0002] Heat dissipation is a key issue in improving the reliability and life of high-power electronic devices. Materials with high thermal conductivity are usually used in components that require effective heat dissipation, such as heat sinks. Due to the characteristics of high thermal conductivity, light weight, and low cost, aluminum and its alloy materials are widely used as heat sink materials. There are three ways of heat dissipation in heat sinks: thermal convection, thermal conduction, and thermal radiation. Among them, radiation heat dissipation has received widespread attention as a passive, efficient, and renewable heat dissipation method. However, the emissivity of aluminum is extremely low, only 0.1-0.2, which inhibits its effective radiation heat dissipation in the infrared region; in addition, aluminum alloys are extremely susceptible to corrosion in extreme environments. Superhydrophobic surface technology can improve this situation, which can provide further protection for multifunctional surfaces. Therefore, it is necessary to develop multifunctional materials with effective radiation heat dissipation capabilities and superhydrophobicity, self-cleaning, and corrosion resistance.
[0003] In order to construct this multifunctional surface, the two-step method, anodic oxidation, CVD method and other methods of combining plasma electrolytic oxidation with electrodeposition and hydrothermal method are currently synthesized. For example, Zou et al. prepared a super-hydrophobic + radiation heat dissipation Al2O3 / CH composite coating by a two-step method combining plasma electrolytic oxidation (PEO) and electrodeposition, while improving heat dissipation and corrosion resistance. However, these methods all have complex processes and the disadvantages of difficult large-scale production. Polymer-based coatings are very popular surface treatment methods, and coating processes are not affected by many factors such as substrate composition, size, roughness and shape. At present, polymer-based coating materials are often applied to radiation heat dissipation or super-hydrophobic coating single fields, but polymer-based coating materials with both heat dissipation and hydrophobic surface characteristics are rarely studied. The present invention comes from this. Summary of the invention
[0004] In order to solve at least one of the above technical problems, an object of the present invention is to provide a super-hydrophobic radiation heat dissipation coating material and a preparation method thereof.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0006] One of the purposes of the present invention is to provide a super-hydrophobic radiation heat dissipation coating material, comprising a TiC@BN composite powder and a polymer binder system, wherein the TiC@BN composite powder accounts for 30% to 70wt% of the polymer binder system by mass percentage; the TiC@BN composite powder has a hierarchical structure, BN nanosheets are wrapped on the surface of TiC particles and the mass proportion of BN is 10wt% to 62.3wt%; the contact angle CA of the super-hydrophobic radiation heat dissipation coating is greater than 150°, the rolling angle is less than 10°, and the average emissivity in the 2.5-25μm band of sunlight is
[0007] Furthermore, the polymer binder system includes a polymer binder selected from the group consisting of polydimethylsiloxane (PDMS), fluorosilicone resin (FSi), and epoxy resin (EP) and a curing agent thereof, wherein the mass ratio of the polymer binder to the curing agent is 10:1.
[0008] Another object of the present invention is to provide a method for preparing the above-mentioned super-hydrophobic radiation heat dissipation coating material, comprising the following steps:
[0009] S1. Weigh raw material powders of titanium powder, boron carbide powder and carbon black according to the mass ratio, add ball milling media (ethanol and zirconium oxide grinding balls, ball-to-material ratio of 4:1, rotation speed of 300 rpm, time of 2-5 hours) to obtain a mixed slurry, and place the mixed slurry in an oven for drying (60-100° C., 12-24 hours) to obtain a dried powder;
[0010] S2, after passing the dried powder through a 20-mesh sieve, placing the powder together in a combustion synthesis reactor, and performing a combustion synthesis reaction under a nitrogen pressure of 1 to 5 MPa to obtain TiC@BN composite powder;
[0011] S3, the TiC@BN composite powder is passed through a 200-mesh sieve and then dispersed in an organic solvent, and ultrasonically dispersed for 30-60 minutes to obtain a dispersion system A;
[0012] S4, adding a polymer binder system to the dispersed system A, wherein the TiC@BN composite powder accounts for 30% to 70wt% of the polymer binder system, and magnetically stirring to obtain a super-hydrophobic radiation heat dissipation coating;
[0013] S5. Coating the super-hydrophobic radiation heat dissipation coating on the surface of the substrate to obtain the super-hydrophobic radiation heat dissipation coating.
[0014] The present invention adopts nitridation combustion synthesis technology, takes Ti, B4C and C as raw materials, and synthesizes TiC@BN composite powder with high emissivity and super hydrophobicity based on chemical reaction equation (1) in a nitrogen atmosphere.
[0015] Ti+B4C+C+N2→TiC+BN (1).
[0016] Furthermore, in step S1, in the raw material powder, in terms of mass percentage, titanium powder accounts for 46.5-76.3wt%, boron carbide powder accounts for 5.9-53.5wt%, and carbon black accounts for 0-17.8wt%. It should be noted that the purpose of the carbon black of the present invention is to regulate the composition of the final composite powder. The reaction of equation (1) can also occur without carbon black as the raw material powder to generate the desired TiC@BN composite powder.
[0017] Furthermore, in step S1, the particle size of the titanium powder is 100-500 mesh, the particle size of the boron carbide powder is 1-10 μm, and the particle size of the carbon black is 0.2-2 μm.
[0018] Further, in step S4, the polymer binder system includes a polymer binder selected from the group consisting of polydimethylsiloxane, fluorosilicone resin, and epoxy resin, and a curing agent thereof, wherein the mass ratio of the polymer binder to its curing agent is 10:1, and the magnetic stirring conditions are a rotation speed of 100 rpm and a temperature of 25° C. Step S4 includes:
[0019] S41, first adding the polymer binder in the polymer binder system to the dispersion system A, and magnetically stirring for 30-60 minutes to obtain the dispersion system B;
[0020] S42, adding the corresponding curing agent into the dispersion system B, and magnetically stirring for 20-30 minutes to obtain the super hydrophobic radiation heat dissipation coating.
[0021] Furthermore, in step S2, the TiC@BN composite powder has a hierarchical structure, BN nanosheets are wrapped on the surface of TiC particles and the mass proportion of BN is 10wt% to 62.3wt%.
[0022] Furthermore, in step S3, the mass ratio of the TiC@BN composite powder to the organic solvent is 1:1 to 1:2, and the organic solvent includes a mixture of one or more of xylene, ethyl acetate, and butyl acetate.
[0023] Furthermore, in step S5, the contact angle CA of the super hydrophobic radiation heat dissipation coating is greater than 150°, the rolling angle is less than 10°, and the average emissivity in the 2.5-25 μm band of sunlight is More preferably, the average infrared emissivity of the super hydrophobic radiation heat dissipation coating in the 2.5-25 μm band of sunlight is Contact angle CA>155°, sliding angle<5°.
[0024] Further, in step S5, the coating is carried out by any one of spraying, scraping and dipping; and / or
[0025] In step S5, the substrate is selected from any one of aluminum sheet, paper, mica sheet, and glass sheet.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The super-hydrophobic radiation heat dissipation coating material of the present invention adopts a short-cycle, near-zero energy consumption nitridation combustion synthesis technology, with Ti, B4C, and C as reaction raw materials, to prepare a TiC@BN composite ceramic powder material with a hierarchical structure under a nitrogen atmosphere, and BN nanosheets are wrapped on the surface of TiC particles. With TiC@BN powder as filler, a radiation heat dissipation coating material with both super-hydrophobicity and high infrared emissivity is prepared, which is expected to achieve efficient and long-term radiation heat dissipation of electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 This is an infrared emission spectrum of the super hydrophobic radiation heat dissipation coating in Example 1 of the present invention at 2.5-25 μm of sunlight;
[0030] Figure 2 : The water contact angle ((a) in the figure) and the sliding angle ((b) in the figure) of the super-hydrophobic radiation heat dissipation coating in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] In view of the deficiencies in the prior art, the inventors of this case, after long-term research and extensive practical discoveries, proposed a super-hydrophobic radiation heat dissipation coating material based on air combustion synthesis and a preparation method thereof.
[0032] The following is a further explanation of the technical solution, its implementation process and principle, etc. in conjunction with the preferred embodiments and the accompanying drawings. It should be noted that the following embodiments are only auxiliary explanations of the present invention and should not be used to limit the protection scope of the present invention.
[0033] Example 1
[0034] Weigh 71.9 g of Ti powder with a particle size of 500 mesh, 12.9 g of B4C powder with a particle size of 3.5 μm, and 15.2 g of carbon black with a particle size of 2 μm and add them into a ball mill. Use anhydrous ethanol as the ball milling medium and zirconium oxide (ZrO2) balls as grinding balls. Ball mill for 2 hours. The mass ratio of grinding balls to raw material powders is 4 / 1. After mixing evenly, dry the obtained mixed slurry at 60°C for 24 hours, dry and sieve to obtain dried powder. The sieved dried powder The powder is loaded into a porous graphite mold and then placed in a 20L combustion synthesis kettle. 5MPa of nitrogen is passed into the combustion synthesis kettle. The tungsten wire buried in the front end of the mold is energized to induce the combustion reaction, and the product is synthesized under the action of the heat released by the reaction itself. The vast majority of particles in the product (denoted as TiC@BN composite powder) have a micro-nano hierarchical structure (BN nanosheets are wrapped on the surface of TiC particles). The particle size of the composite powder is about 3μm, and the mass proportion of BN is 40wt%.
[0035] Afterwards, the TiC@BN / fluorosilicone resin coating was prepared using the product obtained by combustion synthesis, namely TiC@BN composite powder, as filler and fluorosilicone resin as binder: 3 g of TiC@BN composite powder was weighed and ultrasonically dispersed in a mixed solvent of 3 g of ethyl acetate and butyl acetate (mass ratio of 1 / 1), and mixed slurry A, namely dispersion system A, was obtained after uniform dispersion; 6.4 g of fluorosilicone resin was added to dispersion system A, and mixed evenly by magnetic stirring at 300 rpm to obtain mixed slurry B, namely dispersion system B; 0.6 g of fluorosilicone resin curing agent such as aminosilane was added to mixed slurry B, and magnetic stirring was continued to mix to obtain a super-hydrophobic radiation heat dissipation coating; the super-hydrophobic radiation heat dissipation coating was sprayed on an aluminum sheet to obtain a super-hydrophobic radiation heat dissipation coating (referred to as TiC@BN / FSi coating). The coating has a wide-band high infrared emissivity in the 2.5-25 μm band, with an average value of is 0.93, the water contact angle is 155°, and the sliding angle is 5°.
[0036] Example 2
[0037] 71.9 g of Ti powder with a particle size of 100 mesh, 12.9 g of B4C powder with a particle size of 10 μm, and 15.2 g of carbon black with a particle size of 0.2 μm were weighed and added into a ball mill, with anhydrous ethanol as the ball milling medium and ZrO2 balls as grinding balls, and the ball milling was carried out for 2 hours, and the mass ratio of grinding balls to raw material powders was 4 / 1; after uniform mixing, the obtained mixed slurry was dried at a temperature of 60°C for 24 hours, and dried and sieved to obtain a dried powder; the sieved dried powder was loaded into a porous graphite mold and then placed in a 20L combustion synthesis reactor, 5 MPa of nitrogen was passed into the combustion synthesis reactor, and the tungsten wire buried at the front end of the mold was energized to induce a combustion reaction, and the product (referred to as TiC@BN composite powder) was synthesized under the action of the heat released by the reaction itself; the product contained nano- and micro-scale TiC@BN hierarchical structures (BN nanosheets were wrapped on the surface of TiC particles), and the mass of BN accounted for about 40wt%.
[0038] Afterwards, the TiC@BN / fluorosilicone resin coating was prepared using the product obtained by combustion synthesis, namely TiC@BN composite powder, as filler and fluorosilicone resin as binder: 3 g of TiC@BN composite powder was weighed and ultrasonically dispersed in a mixed solvent of 3 g of ethyl acetate and butyl acetate (mass ratio of 1 / 1), and mixed slurry A, namely dispersion system, was obtained after uniform dispersion; 6.4 g of fluorosilicone resin was added to dispersion system A, and mixed uniformly by magnetic stirring at 300 rpm to obtain mixed slurry B, namely dispersion system B; 0.6 g of fluorosilicone resin curing agent such as aminosilane was added to mixed slurry B, and magnetic stirring was continued to mix to obtain super-hydrophobic radiation heat dissipation coating; the super-hydrophobic radiation heat dissipation coating was sprayed on an aluminum sheet to obtain a TiC@BN / FSi coating. The coating has a wide-band high infrared emissivity in the 2.5-25μm band, with an average value of is 0.93, the water contact angle is 156°, and the sliding angle is 4°.
[0039] Example 3
[0040] Weigh 76.3g of Ti powder with a particle size of 500 mesh, 5.9g of B4C powder with a particle size of 3.5μm, and 17.8g of C powder with a particle size of 1μm, and add them into a ball mill, use anhydrous ethanol as the ball milling medium, ZrO2 balls as grinding balls, and ball mill for 2h, and the mass ratio of grinding balls to raw material powders is 4 / 1; after mixing evenly, the obtained mixed slurry is dried at a temperature of 60°C for 24h, and dried and sieved to obtain a dried powder; the sieved dried powder is loaded into a porous graphite mold and placed together in a 20L combustion synthesis reactor, 5MPa of nitrogen is passed into the combustion synthesis reactor, and the tungsten wire buried in the front end of the mold is energized to induce a combustion reaction, and the product is synthesized under the action of the heat released by the reaction itself; the product has a submicron core-shell structure (BN nanosheets are wrapped on the surface of TiC particles), and the mass proportion of BN is 10wt%.
[0041] Afterwards, the TiC@BN / fluorosilicone resin coating was prepared using the product obtained by combustion synthesis, namely TiC@BN composite powder, as filler and FSi as binder: 3 g of TiC@BN composite powder was weighed and ultrasonically dispersed in a mixed solvent of 3 g of ethyl acetate and butyl acetate (mass ratio of 1 / 1), and after uniform dispersion, mixed slurry A, namely dispersion system A, was obtained; 6.4 g of fluorosilicone resin was added to dispersion system A, and mixed evenly by magnetic stirring at 300 rpm to obtain mixed slurry B, namely dispersion system B; 0.6 g of fluorosilicone resin curing agent such as aminosilane was added to mixed slurry B, and magnetic stirring was continued to mix to obtain a super-hydrophobic radiation heat dissipation coating; the super-hydrophobic radiation heat dissipation coating was sprayed on an aluminum sheet to obtain a TiC@BN / FSi coating. The coating has a wide-band high infrared emissivity in the 2.5-25μm band, with an average value of is 0.95, the water contact angle is 150°, and the sliding angle is 9°.
[0042] Example 4
[0043] 71.9 g of Ti powder with a particle size of 500 mesh, 12.9 g of B4C powder with a particle size of 3.5 μm, and 15.2 g of carbon black with a particle size of 2 μm were weighed and added into a ball mill, with anhydrous ethanol as the ball milling medium and ZrO2 balls as grinding balls, and the ball milling was carried out for 2 hours, and the mass ratio of grinding balls to raw material powders was 4 / 1; after uniform mixing, the obtained mixed slurry was dried at 60°C for 24 hours, and dried and sieved to obtain dried powder; the sieved dried powder was loaded into a porous graphite mold and placed together in a 20L combustion synthesis reactor, 5 MPa of nitrogen was passed into the combustion synthesis reactor, and the tungsten wire buried at the front end of the mold was energized to induce the combustion reaction, and the product was synthesized under the action of the heat released by the reaction itself; most of the particles in the product have a micro-nano hierarchical structure, the particle size is about 3 μm, and the mass proportion of BN is 40wt%.
[0044] Afterwards, the product obtained by combustion synthesis, namely TiC@BN composite powder, was used as filler and PDMS was used as binder to prepare TiC@BN / PDMS coating: 7 g of TiC@BN composite powder was weighed and ultrasonically dispersed in a mixed solvent of 14 g of ethyl acetate and butyl acetate (mass ratio of 1 / 1), and mixed slurry A, namely dispersion system A, was obtained after uniform dispersion; 2.7 g of PDMS was added to dispersion system A, and mixed uniformly by magnetic stirring at 300 rpm to obtain mixed slurry B, namely dispersion system B; 0.3 g of PDMS curing agent, such as silane coupling agent methyltrichlorosilane, was added to mixed slurry B, and magnetic stirring was continued to mix to obtain super-hydrophobic radiation heat dissipation coating; the super-hydrophobic radiation heat dissipation coating was scraped on an aluminum sheet to obtain a TiC@BN / PDMS coating. The coating has a wide-band high infrared emissivity in the 2.5-25μm band, with an average value of is 0.96, the water contact angle is 160°, and the sliding angle is 5°.
[0045] Example 5
[0046] 71.9 g of Ti powder with a particle size of 500 mesh, 12.9 g of B4C powder with a particle size of 3.5 μm, and 15.2 g of carbon black with a particle size of 2 μm were weighed and added into a ball mill, with anhydrous ethanol as the ball milling medium and ZrO2 balls as grinding balls, and the ball milling was carried out for 2 hours, and the mass ratio of grinding balls to raw material powders was 4 / 1; after uniform mixing, the obtained mixed slurry was dried at 60°C for 24 hours, and dried and sieved to obtain dried powder; the sieved dried powder was loaded into a porous graphite mold and placed together in a 20L combustion synthesis reactor, 5 MPa of nitrogen was passed into the combustion synthesis reactor, and the tungsten wire buried at the front end of the mold was energized to induce the combustion reaction, and the product was synthesized under the action of the heat released by the reaction itself; most of the particles in the product have a micro-nano hierarchical structure, the particle size is about 3 μm, and the mass proportion of BN is 40wt%.
[0047] Afterwards, the TiC@BN / fluorosilicone resin coating was prepared using the product obtained by combustion synthesis, namely TiC@BN composite powder, as filler and fluorosilicone resin as binder: 7 g of TiC@BN composite powder was weighed and ultrasonically dispersed in a mixed solvent of 14 g of ethyl acetate and butyl acetate (mass ratio of 1 / 1), and after uniform dispersion, mixed slurry A, namely dispersion system A, was obtained; 2.7 g of fluorosilicone resin was added to dispersion system A, and mixed evenly by magnetic stirring at 300 rpm to obtain mixed slurry B, namely dispersion system B; 0.3 g of fluorosilicone resin, such as a curing agent such as aminosilane, was added to mixed slurry B, and magnetic stirring was continued to mix to obtain a super-hydrophobic radiation heat dissipation coating; the super-hydrophobic radiation heat dissipation coating was dip-coated on a glass sheet to obtain a TiC@BN / FSi coating. The coating has a wide-band high infrared emissivity in the 2.5-25μm band, with an average value of is 0.93, the water contact angle is 155°, and the sliding angle is 4°.
[0048] Example 6
[0049] Weigh 48.5g of Ti powder with a particle size of 500 mesh, 50.4g of B4C powder with a particle size of 3.5μm, and 1.1g of carbon black with a particle size of 2μm, and add them into a ball mill, use anhydrous ethanol as the ball milling medium, ZrO2 balls as grinding balls, and ball mill for 2h, and the mass ratio of grinding balls to raw material powders is 4 / 1; after mixing evenly, dry the obtained mixed slurry at 60°C for 24h, and obtain dried powder after drying and sieving; the sieved dried powder is loaded into a porous graphite mold and placed in a 20L combustion synthesis reactor, 5MPa of nitrogen is passed into the combustion synthesis reactor, and the tungsten wire buried at the front end of the mold is energized to induce the combustion reaction, and the product is synthesized under the action of the heat released by the reaction itself; most of the particles in the product have a micro-nano hierarchical structure, the particle size is about 3μm, and the mass proportion of BN is 60wt%.
[0050] Afterwards, the TiC@BN / fluorosilicone resin coating was prepared using the product obtained by combustion synthesis, namely TiC@BN composite powder, as filler and fluorosilicone resin as binder: 3 g of TiC@BN composite powder was weighed and ultrasonically dispersed in a mixed solvent of 3 g of ethyl acetate and butyl acetate (mass ratio of 1 / 1), and after uniform dispersion, mixed slurry A, namely dispersion system A, was obtained; 6.4 g of fluorosilicone resin was added to dispersion system A, and mixed evenly by magnetic stirring at 300 rpm to obtain mixed slurry B, namely dispersion system B; 0.6 g of fluorosilicone resin curing agent such as aminosilane was added to mixed slurry B, and magnetic stirring was continued to mix to obtain a super-hydrophobic radiation heat dissipation coating; the super-hydrophobic radiation heat dissipation coating was sprayed on the mica sheet to obtain a TiC@BN / FSi coating. The coating has a wide-band high infrared emissivity in the 2.5-25μm band, with an average value of is 0.91, the water contact angle is 153°, and the sliding angle is 5°.
[0051] Example 7
[0052] Weigh 46.5g of Ti powder with a particle size of 500 mesh and 53.5g of B4C powder with a particle size of 3.5μm, and add them into a ball mill, use anhydrous ethanol as the ball milling medium, ZrO2 balls as grinding balls, and ball mill for 2h. The mass ratio of grinding balls to raw material powders is 4 / 1. After mixing evenly, dry the obtained mixed slurry at 60°C for 24h, and obtain dried powder after drying and screening. The sieved dried powder is loaded into a porous graphite mold and placed in a 20L combustion synthesis reactor. 5MPa of nitrogen is passed into the combustion synthesis reactor, and the tungsten wire buried at the front end of the mold is energized to induce the combustion reaction, and the product is synthesized under the action of the heat released by the reaction itself. Most of the particles in the product have a micro-nano hierarchical structure, the particle size is about 3μm, and the mass proportion of BN is 62.3wt%.
[0053] Afterwards, the TiC@BN / fluorosilicone resin coating was prepared using the product obtained by combustion synthesis, namely TiC@BN composite powder, as filler and fluorosilicone resin as binder: 3 g of TiC@BN composite powder was weighed and ultrasonically dispersed in a mixed solvent of 3 g of ethyl acetate and butyl acetate (mass ratio of 1 / 1), and after uniform dispersion, mixed slurry A, namely dispersion system A, was obtained; 6.4 g of fluorosilicone resin was added to dispersion system A, and mixed evenly by magnetic stirring at 300 rpm to obtain mixed slurry B, namely dispersion system B; 0.6 g of fluorosilicone resin curing agent such as aminosilane was added to mixed slurry B, and magnetic stirring was continued to mix to obtain a super-hydrophobic radiation heat dissipation coating; the super-hydrophobic radiation heat dissipation coating was sprayed on paper to obtain a TiC@BN / FSi coating. The coating has a wide-band high infrared emissivity in the 2.5-25μm band, with an average value of is 0.90, the water contact angle is 154°, and the sliding angle is 4°.
[0054] Comparative Example 1
[0055] 78.2 g of Ti powder with a particle size of 500 mesh, 2.9 g of B4C powder with a particle size of 3.5 μm, and 18.9 g of carbon black with a particle size of 2 μm were weighed and added into a ball mill, with anhydrous ethanol as the ball milling medium and ZrO2 balls as grinding balls, and the ball milling was carried out for 2 hours, and the mass ratio of grinding balls to raw material powders was 4 / 1; after uniform mixing, the obtained mixed slurry was dried at a temperature of 60°C for 24 hours, and dried and sieved to obtain a dried powder; the sieved dried powder was loaded into a porous graphite mold and placed together in a 20L combustion synthesis reactor, 5 MPa of nitrogen was passed into the combustion synthesis reactor, and the tungsten wire buried at the front end of the mold was energized to induce a combustion reaction, and the product was synthesized under the action of the heat released by the reaction itself; most of the particles in the product have a micro-nano hierarchical structure, a particle size of about 3 μm, and the mass of BN accounts for 5wt% (much lower than Examples 1 to 7).
[0056] Afterwards, the TiC@BN / fluorosilicone resin coating was prepared using the product obtained by combustion synthesis, namely TiC@BN composite powder, as filler and fluorosilicone resin as binder: 7 g of TiC@BN composite powder was weighed and ultrasonically dispersed in a mixed solvent of 14 g of ethyl acetate and butyl acetate (mass ratio of 1 / 1), and mixed slurry A, namely dispersion system A, was obtained after uniform dispersion; 2.7 g of fluorosilicone resin was added to dispersion system A, and mixed evenly by magnetic stirring at 300 rpm to obtain mixed slurry B, namely dispersion system B; 0.3 g of fluorosilicone resin curing agent such as aminosilane was added to mixed slurry B, and magnetic stirring was continued to mix to obtain a super-hydrophobic radiation heat dissipation coating; the super-hydrophobic radiation heat dissipation coating was dip-coated on a glass sheet to obtain a TiC@BN / FSi coating. The coating has a wide-band high infrared emissivity in the 2.5-25μm band, with an average value of The relative humidity of the radiant heat dissipation coating is 0.91, and the water contact angle is 110° (the hydrophobicity is also far inferior to that of Examples 1 to 7). By comparing Comparative Example 1 with Examples 1 to 7, it can be seen that although the infrared emissivity of the radiant heat dissipation coating obtained by the method of Comparative Example 1 is not much different from that of Examples 1 to 7, the hydrophobicity is far inferior to that of Examples 1 to 7, that is, it is impossible to have both high infrared emissivity and strong hydrophobicity at the same time, thereby proving the rationality of the selection of the ratio of the raw material powders (titanium powder, boron carbide powder and carbon black).
[0057] It should be noted that the test methods involved in the above embodiments can all refer to the existing national standards, industry standards or enterprise standards, and will not be described in detail.
[0058] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0059] The use of headings and sections in this disclosure is not meant to limit the disclosure; each section may apply to any aspect, embodiment, or feature of the disclosure.
[0060] Throughout this disclosure, where a composition is described as having, containing, or comprising particular components, or where a process is described as having, containing, or comprising particular process steps, it is contemplated that the compositions taught by the present invention also consist essentially of or consist of the recited components, and that the processes taught by the present invention also consist essentially of or consist of the recited process steps.
[0061] Unless specifically stated otherwise, use of the terms "include," "includes," "including," "have," "has," or "having" should generally be construed as open ended and non-limiting.
[0062] It should be understood that the order of the various steps or the order in which a particular action is performed is not very important, as long as the teachings of the present invention remain operable. In addition, two or more steps or actions may be performed simultaneously.
[0063] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.
Claims
1. A super-hydrophobic radiation heat dissipation coating material, characterized in that: The invention comprises a TiC@BN composite powder and a polymer binder system, wherein the TiC@BN composite powder accounts for 30% to 70wt% of the polymer binder system in terms of mass percentage; the TiC@BN composite powder has a hierarchical structure, BN nanosheets are wrapped on the surface of TiC particles, and the mass percentage of BN is 10wt% to 62.3wt%; the contact angle CA of the super-hydrophobic radiation heat dissipation coating is greater than 150°, the rolling angle is less than 10°, and the average emissivity in the 2.5-25μm band of sunlight is 2. The super-hydrophobic radiation heat dissipation coating material according to claim 1, characterized in that: The polymer binder system comprises a polymer binder selected from the group consisting of polydimethylsiloxane, fluorosilicone resin and epoxy resin and a curing agent thereof, wherein the mass ratio of the polymer binder to the curing agent is 10:
1.
3. A method for preparing a super-hydrophobic radiation heat dissipation coating material, characterized in that: The following steps are involved: S1. Weigh raw material powders of titanium powder, boron carbide powder and carbon black according to mass ratio, add ball milling medium to mix and obtain mixed slurry, and place the mixed slurry in an oven for drying to obtain dried powder; S2, sieving the dried powder and placing them in a combustion synthesis reactor, and performing a combustion synthesis reaction under a nitrogen pressure of 1 to 5 MPa to obtain TiC@BN composite powder; S3, the TiC@BN composite powder is passed through a 200-mesh sieve and then dispersed in an organic solvent, and ultrasonically dispersed for 30-60 minutes to obtain a dispersion system A; S4, adding a polymer binder system to the dispersed system A, wherein the TiC@BN composite powder accounts for 30% to 70wt% of the polymer binder system, and magnetically stirring to obtain a super-hydrophobic radiation heat dissipation coating; S5. Coating the super-hydrophobic radiation heat dissipation coating on the surface of the substrate to obtain the super-hydrophobic radiation heat dissipation coating.
4. The preparation method according to claim 3, characterized in that: In step S1, in the raw material powder, based on the mass percentage, the titanium powder accounts for 46.5-76.3wt%, the boron carbide powder accounts for 5.9-53.5wt%, and the carbon black accounts for 0-17.8wt%.
5. The preparation method according to claim 3, characterized in that: In step S1, the particle size of the titanium powder is 100-500 mesh, the particle size of the boron carbide powder is 1-10 μm, and the particle size of the carbon black is 0.2-2 μm.
6. The preparation method according to claim 3, characterized in that: In step S4, the polymer binder system includes a polymer binder selected from the group consisting of polydimethylsiloxane, fluorosilicone resin, and epoxy resin, and a curing agent thereof, wherein the mass ratio of the polymer binder to its curing agent is 10:
1. Step S4 includes: S41, first adding the polymer binder in the polymer binder system to the dispersion system A, and magnetically stirring for 30-60 minutes to obtain the dispersion system B; S42, adding the corresponding curing agent into the dispersion system B, and magnetically stirring for 20-30 minutes to obtain the super hydrophobic radiation heat dissipation coating.
7. The preparation method according to claim 3, characterized in that: In step S2, the TiC@BN composite powder has a hierarchical structure, BN nanosheets are wrapped on the surface of TiC particles, and the mass proportion of BN is 10wt% to 62.3wt%.
8. The preparation method according to claim 3, characterized in that: In step S3, the mass ratio of the TiC@BN composite powder to the organic solvent is 1:1 to 1:2, and the organic solvent includes a mixture of one or more of xylene, ethyl acetate, and butyl acetate.
9. The preparation method according to claim 3, characterized in that: In step S5, the super hydrophobic radiation heat dissipation coating has a contact angle CA>150°, a rolling angle <10°, and an average emissivity in the 2.5-25 μm band of sunlight.
10. The preparation method according to claim 3, characterized in that: In step S5, the coating is carried out by any one of spraying, scraping and dipping; and / or In step S5, the substrate is selected from any one of aluminum sheet, paper, mica sheet, and glass sheet.